Time for university educators to embrace student videography. Issue 6 (2nd November 2019) - Jorm, Christine; Roberts, Chris; Gordon, Christopher; Nisbet, Gillian; Roper, Lucinda
ABSTRACT: The authors provide an interdisciplinary investigation of student videography for assessment in higher education. Video is becoming a dominant communication modality in our world; school students are taught to create and critique it and educators employ it on-line. Yet the opportunity to include appropriate video-based assessments that capture integrated graduate attributes has been largely missed in higher education. The authors reflect on a health professional student case study which illustrates how video enables students to powerfully demonstrate achievement against learning outcomes: they used filmic techniques to display empathy, patient centred collaboration and interprofessional communication. They also reflect on the barriers to video-based assessment raised by academics. Finally, they call upon leaders in higher education to recognise the utility of multi-media approaches to assessment of complex but critical graduate skills such as communication, digital literacy and interdisciplinarity, in addition to demonstrating the application of disciplinary knowledge to relevant and authentic problems.